The Association Between Glymphatic System Dysfunction and Cognitive Impairment in Cerebral Small Vessel Disease - Tang, Jie; Zhang, Miaoyi; Liu, Na; Xue, Yang; Ren, Xue; Huang, Qi; Shi, Langfeng; Fu, Jianhui (Frontiers in Aging Neuroscience, 2022)
The mechanism of cognitive impairment in patients with cerebral small vessel disease (CSVD) remains unknown. Glymphatic system dysfunction, which has been proven to influence cognitive impairment, can be evaluated by diffusion tensor image analysis along the perivascular space (ALPS index). We explored whether cognitive impairment in CSVD is associated with glymphatic clearance dysfunction. One hundred and thirty-three CSVD patients were enrolled and received neuropsychological test batteries and magnetic resonance imaging. They then categorized into CSVD with cognitive impairment (CSVD-CI) and the cognitively normal CSVD (CSVD-CN) groups. ALPS-index and the CSVD markers white matter lesions (WMLs), cerebral microbleeds, lacunes and perivascular space (PVS) were aslo assessed. Univariate analysis shown ALPS-index between the CSVD-CN (n=50) and CSVD-CI group (n=83) has significant difference (P<0.001). And this difference remains significant (95% CI<0.001 to 0.133) after adjusting for age, education, hypertension and diabetes, smoking, alcohol abuse six risk factors and the CSVD markers. ALPS-index was independently linearly correlated with global cognitive function, executive function, attention function, and memory after adjusting for aforementioned six risk factors or the CSVD markers. Our results suggest glymphatic system impairment is independently related to cognitive impairment in CSVD patients.